Potency of Endophytic and Rhizospheric Bacteria of Akar Kucing (Acalypha indica Linn.)as Antibacteria against Klebsiella pneumoniae - Fitriana Dewi Rahmawati; Suharjono (Journal of Tropical Life Science, 2021)
The prevalence of pneumonia in Indonesia was 2% in 2018. Treatment of pneumonia using antibiotics caused resistancetopathogenic bacteria.Endophytic and rhizo-sphericbacteria from the medicinal plant AcalyphaindicaLinn., is a new type of bac-teria that producesantibacterial compounds against Klebsiella pneumoniae. This study aims to analyze the potency and identify endophytic and rhizospheric bacteria of the A.indicaLinn as an antibacterial of K.pneumoniae. The research includes iso-lation and purification of endophytic and rhizospheric bacteria of the A. indicaLinn, antagonistic assay of bacteria cell culture, antibacterial assay of bacteria metabolites, and identificationof potential isolates based on 16S rDNA sequencesimilarity. The results showed that number of rhizosphere bacteria 6.83 ×105CFU/g was more than endophytic bacteria 1.78 ×104 CFU/g. Diversity of rhizosphere bacterial 0.72 was higher than endophytic bacteria 0.62. The rhizospheric bacteria RU112B and RU315B had the highest activity to inhibit the growth of K.pneumoniae. Both isolates RU112B and RU315B were identified as Staphylococcus saprophyticuswith a similarity 99.83% and Luteimonas terrae with a similarity 99.67% respectively